Report on small-scale irrigation’s contributions to increased income, economic growth and market opportunities - Feed the Future Innovation Lab for Small Scale Irrigation (Feed the Future Innovation Lab for Small Scale Irrigation, 2023)
Farmers, entrepreneurs, and businesses are already leading the way by expanding irrigation in response to climate variability and the growing demand for vegetables and fruit through supplemental and dry-season irrigated production. Increasing commercialization creates market opportunities throughout irrigated value chains. The Feed the Future Innovation Lab for Small Scale Irrigation (ILSSI), has supported research and partnerships with companies and producer groups to innovate technologies, share information, and develop inclusive, market-based approaches that catalyze investment in irrigation.